EXPLORING THE INFLUENCE OF FAMILY SUPPORT AND OCCUPATIONAL SAFETY ON WORK-LIFE BALANCE AMONG WOMEN NURSES IN GOVERNMENT HOSPITALS IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Balancing professional responsibilities with personal life is a significant challenge for women nurses, especially in government hospitals where the demands are high. This research explores how family support and occupational safety impact the work-life balance of women nurses in Thoothukudi District. Employing a structured survey with 130 participants, the study utilized descriptive statistics to summarize responses, Chi-Square analysis to assess the relationship between family support, workplace safety, and stress levels, and Pearson correlation coefficients to examine the impact on job performance and commitment. Findings reveal that strong family support helps manage work-related stress and improves job focus, while adequate safety measures reduce burnout and enhance job satisfaction. The analysis shows positive correlations between high levels of family support and workplace safety with better job performance and commitment. Recommendations include improving family communication and safety protocols to better support nurses' well-being and job satisfaction.